Penerapan Manajemen Strategis Dalam Menghadapi Perubahan Struktural Dan Kultural Di Sekolah - Muh Thoriq Aziz Kusuma; Imam Mujahid; Usman Abu Bakar (Journal of Humanities, Social Sciences, and Education, 2025)
In the context of an ever-changing environmental dynamic, educational institutions are required to continuously adapt in a sustainable manner. This article discusses how strategic management can be employed as a comprehensive framework to understand and manage the complex interactions between structural and cultural changes within the school environment. Through a qualitative approach based on a literature study, this research highlights that the process of institutional transformation does not occur linearly but is dialectical and full of dynamics. The analysis reveals that structural measures, such as the implementation of new technologies or curriculum updates, often clash with the deeply rooted organizational culture, including established value systems, norms, and long-standing practices. Resistance or rejection arising from these changes should not be viewed as obstacles but rather as important indicators reflecting underlying tensions within the system. By adopting perspectives from Complex Adaptive Systems (CAS) theory, Activity Theory, and dialectical approaches, this article emphasizes the importance of strategic leadership in managing and aligning these contradictions to promote sustainable and internally ingrained change. The main conclusion of this study is that leaders in the education sector need to shift from a control- and managerial-based leadership style toward an adaptive, facilitative approach that empowers all members of the school community as key agents in the transformation process.